The association between psychotic experiences and health-related quality of life. A cross-national analysis based on World Mental Health Surveys (2018)
Psychotic experiences (PEs)are associated with arrange of mental and physical disorders, and disability, but little is known about the association between PEs and aspects of health-related quality of life (HRQoL). We aimed to investigate the association between PEs and five HRQoL indicators with various adjustments. Using data from the WHO World Mental Health surveys (n = 33,370 adult respondents from 19 countries), we assessed for PEs and five HRQoL indicators (self-rated physical or mental health, perceived level of stigma (embarrassment and discrimination), and social network burden). Logistic regression models that adjusted for socio-demographic characteristics, 21 DSM-IV mental disorders, and 14 general medical conditions were used to investigate the associations between the variables of interest. We also investigated dose-response relationships between PE related metrics (number of types and frequency of episodes) and the HRQoL indicators. Those with a history of PEs had increased odds of poor perceived mental (OR = 1.5, 95% CI = 1.2–1.9) and physical health (OR = 1.3, 95% CI =1.0–1.7) after adjustment for the presence of any mental or general medical conditions. Higher levels of perceived stigma and social network burden were also associated with PEs in the adjusted models. Dose response associations between PE type and frequency metrics and subjective physical and mental health were non-significant, except those with more PE types had increased odds of reporting higher discrimination (OR=2.2,95%CI=1.3–3.5). Our findings provide novel insights into how those with PEs perceive their health status.